2018
DOI: 10.1002/jcp.26916
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells as a therapeutic target in bladder cancer

Abstract: Bladder cancer is one of the most prevalent genitourinary cancers responsible for about 150,000 deaths per year worldwide. Currently, several treatments, such as endoscopic and open surgery, appended by local or systemic immunotherapy, chemotherapy, and radiotherapy are used to treat this malignancy. However, the differences in treatment outcome among patients suffering from bladder cancer are considered as one of the important challenges. In recent years, cancer stem cells, representing a population of undiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 103 publications
(146 reference statements)
2
41
0
1
Order By: Relevance
“…Although many studies have focused on BRCA diagnosis and treatment in recent years, therapeutic strategies to prevent and treat this malignancy are still inadequate and ineffective. With the emergence of the tumour CSC hypothesis, cancer cells are now considered likely to originate from a cell population called stem cells, which has self-renewal capacity; in addition, CSCs have been reported to be involved in tumour progression, therapeutic resistance and recurrence [15]. Thus, it is fairly important and urgent to identify the key genes driving the crucial cellular processes involved in the transformation from quiescent stem cells to non-renewing cancer cells with unlimited proliferative potential.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have focused on BRCA diagnosis and treatment in recent years, therapeutic strategies to prevent and treat this malignancy are still inadequate and ineffective. With the emergence of the tumour CSC hypothesis, cancer cells are now considered likely to originate from a cell population called stem cells, which has self-renewal capacity; in addition, CSCs have been reported to be involved in tumour progression, therapeutic resistance and recurrence [15]. Thus, it is fairly important and urgent to identify the key genes driving the crucial cellular processes involved in the transformation from quiescent stem cells to non-renewing cancer cells with unlimited proliferative potential.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells are the cellular sources of unlimited proliferation and recurrence of malignant tumors. It is reported that tumor stem cells are involved in the process of tumor cell proliferation, invasion, metastasis, and therapeutic resistance [ 25 ], which ultimately predicts the low survival rate. Generally, CSCs are resistant to currently available treatments [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we observed that mRNAsi tend to increase with the progression of tumor grade and stage, indicating that the number of CSCs in cancer tissue increases as the tumor progression, which is consistent with the characteristic of CSCs promoting the malignant process of cancer cells. 25 In view of the close relationship between CSCs and tumor formation or development, we constructed a weighted gene co-expression network to screen genes related to the CSCs characteristic to explore the molecular mechanism of CSCs affecting the formation and development of HNSCC. The GO functional enrichment analysis showed that genes in turquoise module mainly participated in DNA replication, chromatin assembly, mitosis.…”
Section: Discussionmentioning
confidence: 99%